Anak Membutuhkan Penegak Hukum Humanis (Analisis Putusan MK Nomor 1/PUU-VIII/2010) - Satriya, Bambang (Mahkamah Konstitusi Republik Indonesia, 2011)
The case number 1/PPU-VIII/2010 which has been decided by the Constitutional Court (MK) might become a precious experience for each part which gains trust to protect children. The verdict given by the Constitutional Court not only determines the limitation of the children age which has problems with law who must be demanded for an account, but also place children as a subject whose rights must be protected from the practice of ignorance, violence, violation, and any other cruelty.